Représentations de la migration dans le roman graphique Madgermanes - Maksa, Gyula; Murányi, Kata (Acta Romanica Quinqueecclesiensis : La publication du Département d'Études Françaises et Francophones, Université de Pécs, 2025)
Birgit Weyhe’s Madgermanes (2016) is a graphic novel depicting the experiences of Mozambican contract workers in East Germany between 1979 and 1990. Through the intertwined stories of José, Basilio, and Anabella, Weyhe explores migration, acculturation, racism, and the search for belonging across socialist and post-socialist contexts. Blending documentary realism with expressive visuals, the novel portrays both the promises and disillusionments of “brotherly” socialist cooperation. Madgermanes stands as an Afropolitan narrative that bridges African and European perspectives, highlighting hybridity, cultural displacement, and the problem of identity in a globalized, postcolonial world.